Invisible Stanley - Brown, Jeff, 1926-; Nash, Scott (New York, N.Y. : HarperTrophy, 2003)
One morning after a thunderstorm, the Lambchop family is surprised to discover that Stanley is suddenly invisible.
Keywords: Stanley (Fictitious character : Brown) -- Juvenile fiction; Brothers -- Juvenile fiction; Family -- Juvenile fiction; Humorous fiction